Dynamic response of a damaging masonry wall. (2017) - Addessi, Daniela; Gatta, Cristina; Vestroni, Fabrizio
Abstract: A nonlocal damage-plastic model is adopted to describe the nonlinear structural response of masonry structures. The model, based on a macromechanical approach, accounts for strength and stiffness degradation with hysteretic dissipation typically characterizing the masonry response, when it is subjected to horizontal loads. The stiffness recovery due to the crack closure, under cyclic loading, is also introduced by defining two different scalar damage variables for prevailing tensile and compressive states. To explore the effect of such nonlinear phenomena on the masonry structural response, the behavior of an unreinforced slender wall is investigated in the dynamic field. Special attention is devoted to the analysis of the wall frequency response curves (FRCs), obtained by imposing base harmonic accelerations with slowly time-variable frequency. These curves highlight the complexity of the dynamic phenomenon: due to the stiffness decay exhibited by the wall, a continuous variation of its natural frequencies occurs, which in turn modifies the resonance conditions. Finally, the wall response results strongly path-dependent and the characteristics of the wall restoring force lead to multi-valued FRCs.